Isolation and Identificationof Bacteriocin by Dairy Products - Maryam Aslam, Furqan Ali Shah, Hassan Farooq, Gul Hassan, Mizhgan Ovais Khan, Syed Hasnain Shah, Gadhir Ali, Irfan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Bacteriocins is an antimicrobial substances produced by bacteria, identified by lactic acid bacteria (LAB) which has been used as food bio-preservatives. The study was conducted at “Department of Life sciences, University of Management and Technology,” Lahore, Pakistan and was aimed to isolates and identify bacteriocin producing bacterial from milk and yogurt.A total of 30 samples were collected (milk n=15; yogurt n= 14)from different local areas of Lahore. All the samples were serially diluted (10-1 to 10-7) and processed on nutrient agar by spread plate method for 24 h at 37℃. All the isolates wereidentified through colony morphology on agar plates, Gram stain reaction and different biochemical tests such as catalase, oxidase, coagulase and indole respectively. Bacillus subtilis and Escherichia coli were used as sensitive indicator bacteria towards bacteriocin producing species. Out 87 isolates, 30 were found as bacteriocin producers. Out of 30 producer species, 45% were from milk and 24% were from yogurt samples. The prominent producer isolates were Lactobacillus (40%),Lactococcusspp. (17%) and Enterococcus spp. (7%) respectively. Good inhibitory activity was observed against indicator species such as B. subtilis whereas; it was moderate against E. coli. The result indicated that the raw milk as a potential source of bacteriocin producing bacteria. Further research should be done on molecular level of bacterial isolates from dairy products. Keywords: Bacteriocin, Bio-preservatives, Lactic acid bacteria, Antimicrobial activity